Factors associated with prolonged hospitalization of patients with corona virus disease (COVID‑19) in Uganda: a retrospective cohort study - Ingabire, Prossie M.; Nantale, Ritah; Sserwanja, Quraish; Nakireka, Susan; Musaba, Milton W.; Muyinda, Asad; Tumuhaise, Criscent; Namulema, Edith; Bongomin, Felix; Napyo, Agnes; Ainembabazi, Rozen; Olum, Ronald; et al. (Tropical Medicine and Health, 2022)
Identification of factors predicting prolonged hospitalization of patients with coronavirus disease (COVID-19) guides the planning, care and flow of patients in the COVID-19 Treatment Units (CTUs). We determined the length of hospital stay and factors associated with prolonged hospitalization among patients with COVID-19 at six CTUs in Uganda. Methods: We conducted a retrospective cohort study of patients admitted with COVID-19 between January and December 2021 in six CTUs in Uganda. We conducted generalized linear regression models of the binomial family with a log link and robust variance estimation to estimate risk ratios of selected exposure variables and prolonged hospitalization (defined as a hospital stay for 14 days or more). We also conducted negative binomial regression models with robust variance to estimate the rate ratios between selected exposures and hospitalization duration. Results: Data from 968 participants were analyzed. The median length of hospitalization was 5 (range: 1–89) days. A total of 136/968 (14.1%: 95% confidence interval (CI): 11.9–16.4%) patients had prolonged hospitalization. Hospitalization in a public facility (adjusted risk ratio (ARR) = 2.49, 95% CI: 1.65–3.76), critical COVID-19 severity scores (ARR = 3.24: 95% CI: 1.01–10.42), and malaria co-infection (adjusted incident rate ratio (AIRR) = 0.67: 95% CI: 0.55–0.83) were associated with prolonged hospitalization. Conclusion: One out of seven COVID-19 patients had prolonged hospitalization. Healthcare providers in public health facilities should watch out for unnecessary hospitalization. We encourage screening for possible co-morbidities such as malaria among patients admitted for COVID-19.
Keywords: Prolonged hospitalization; Length of hospital stay; COVID-19